The Dynamics of Automobile Demand (Book). - Huegy, Harvey W. (The Accounting Review, 1939)
Reviews the book "The Dynamics of Automobile Demand," by S.L. Horner, C.F. Roos, Victor Von Szeliski, A.T. Court and S.M. DuBrul.